Development Electronic Worksheet MPPj ETHNO-STEAM to Increase Numeracy Literacy and Conservation Character - Fikrina, Qorry Adilla; Sudarmin, Sudarmin; Pujiastuti, Rr Sri Endang; Priatmoko, Sigit; Mahatmanti, F Widhi; Ulfana, Avia Rizka; Kholis, Nur (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
This research aims to develop and analyze the characteristics, feasibility, practicality, and effectiveness of the MPPj ethno-STEAM e-LKPD to improve students' numeracy literacy and conservation character. MPPj is an abbreviation for Project Learning Model, a learning model based on PjBL. The research uses the Research and Development (R&D) method, with the approach model used being the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The analysis stage was carried out to determine students' needs for teaching materials through interviews with teachers. The design stage is carried out to create a design for the e-LKPD. The development stage was carried out to develop research instruments. The instruments in this research include test instruments and non-test instruments. The implementation stage is carried out for product testing. The trials were carried out three times, namely small-scale trials to test the validity and reliability of the instrument and product feasibility, large-scale trials for practicality and effectiveness, and finally, implementation trials to determine the practicality and effectiveness of the final product. The evaluation stage is carried out to analyze the results of product implementation. The research results show (1) the characteristics of e-LKPD, (2) the product is suitable for use based on the results of feasibility tests by material experts and media experts, (3) the product is declared practical based on the results of the practicality questionnaire analysis by teachers and students, (4) the product is effectively used to develop numeracy literacy with indicators of estimating and calculating, using fractions, recognizing and using patterns, using spatial reasoning, using measurements, interpreting statistical information analyzed based on N-gain results, effectively developing conservation character based on the results of analysis of observation sheets with conservation indicators, namely caring, creativity, love of the country, responsibility, caring for the environment, using wisely and effectively in MPPj ethno-STEAM based on the results of the analysis of the project assessment sheet.